Konsep Dasar Masyarakat Dalam Persfektif Ibnu Khaldun - Elen Safitri; Kartina Anggraini Nasution; Khairan Syaputra Tarigan (Comit: Communication, Information and Technology Journal, 2024)
Ibn Khaldun was an Islamic scientist and scientist whose thoughts and ideas were considered reliable in his time. His ideas about society as outlined in his work entitled "Muqaddimah" can help in solving social problems. According to Ibn Khaldun, society is a group of people involved in worldly activities. It is a fundamental trait of human nature to form strong bonds. This study discusses the basic concept of society according to Ibn Khaldun's view. When collecting material, the author uses library research. That is, we collect information, whether in the form of books, journals or other forms, which are directly related to the author's research topic. This study obtains that the conclusion of society in the perspective of Ibn Khaldun is a group of people who contribute in carrying out their activities as movers on earth. Ibn Khaldun divides society into two main parts. First, the Bedouin community. Second, the city community, which has a lazy nature, settles down, develops. Between the two communities, conflicts often occur due to a sense of solidarity, economic factors, and political factors. Keywords: Human, Society, and Ibn Khaldun